Fire Breakers: Novel Devices for the Control of Forest Surface Fires - Awadhiya, Ankur (Indian Forester, 2017)
This paper analyses the issues present with contemporary fire lines, and introduces fire breakers as novel devices for the control of surface forest fires. Field studies done in Mandla and Balaghat districts of Madhya Pradesh demonstrated the phenomena of bleeding, infiltration, repopulation and mosaicking present with the contemporary traditional fire lines. While bleeding results in the burning of adjacent patches of forests that the fire line originally intended to protect, the phenomena of infiltration, repopulation and mosaicking, by providing continuity of fuel, greatly disrupt the efficacy of traditional forest fire lines to act as fire breaks when forest fires do occur. Simulation studies done with the fire breakers introduced in this study vividly demonstrated their efficacy in countering infiltration vis-a-vis traditional fire lines. Besides, by acting as adjuvant fire breaks and permitting frequent burning operations, they help abate the impacts of repopulation and mosaicking. A concurrent use of fire breakers and traditional fire lines can thus greatly enhance our ability to control and manage forest fires.